2012
DOI: 10.1038/hr.2012.102
|View full text |Cite
|
Sign up to set email alerts
|

Long-chain n-3 polyunsaturated fatty acids and blood pressure

Abstract: A large body of evidence from experimental, clinical and epidemiological research has demonstrated the potential benefits of long-chain n-3 polyunsaturated fatty acids (PUFAs), eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) for cardiovascular health, such as anti-atherogenic effects, plaque stability effects, improvement of endothelial or platelet function and anti-arrhythmic effects. 1 These beneficial effects of n-3 PUFA are derived from a myriad of molecular pathways, including alteration of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Omega-3 polyunsaturated fatty acids (n-3 PUFAs) are a family of fatty acids (FAs) with at least three double bonds and the first one at the third carbon atom from the methyl end of the carbon chain. n-3 PUFAs, which include α-linolenic acid (ALA, C18:3), eicosapentaenoic acid (EPA, C20:5), docosapentaenoic acid (DPA, C22:5), and docosahexaenoic acid (DHA, C22:6), are essential nutrients for humans and their health benefits have been well documented, such as inflammation alleviation, visual and neurological development, and prevention of cardiovascular diseases. Among these n-3 PUFAs, EPA, DPA and DHA are more beneficial than the shorter-chain ALA . Even though ALA can be converted into EPA and DHA in the human body, the conversion efficiency is limited .…”
Section: Introductionmentioning
confidence: 99%
“…Omega-3 polyunsaturated fatty acids (n-3 PUFAs) are a family of fatty acids (FAs) with at least three double bonds and the first one at the third carbon atom from the methyl end of the carbon chain. n-3 PUFAs, which include α-linolenic acid (ALA, C18:3), eicosapentaenoic acid (EPA, C20:5), docosapentaenoic acid (DPA, C22:5), and docosahexaenoic acid (DHA, C22:6), are essential nutrients for humans and their health benefits have been well documented, such as inflammation alleviation, visual and neurological development, and prevention of cardiovascular diseases. Among these n-3 PUFAs, EPA, DPA and DHA are more beneficial than the shorter-chain ALA . Even though ALA can be converted into EPA and DHA in the human body, the conversion efficiency is limited .…”
Section: Introductionmentioning
confidence: 99%
“…A large body of evidence from experimental, clinical and epidemiological research has also demonstrated the potential benefits of ω-3 fatty acids, such as EPA on cardiovascular health, including anti-atherogenic, anti-arrhythmic, and plaque stability effects, as well as the improvement of endothelial/platelet function. Besides, ω-3 fatty acids are able to switch arachidonic acid-derived eicosanoid profiles and convert ω-3 fatty acids to vasodilators and platelet anti-coagulation factors (38).…”
Section: Discussionmentioning
confidence: 99%